Kepribadian Neurotik Tokoh Utama Ryuhei Sasaki dalam Naskah Film Tokyo Sonata Karya Sutradara Kiyoshi Kurosawa - Lubistira, Dwi; Wahyuningsih, Tri Mulyani (KIRYOKU, 2025)
The research is about the neurotic personality of the main character Ryuhei Sasaki in the film script "Tokyo Sonata" by director Kiyoshi Kurosawa. The research used qualitative descriptive research approach. The purpose of the study is to describe Ryuhei Sasaki's character using Karen Horney's psychoanalysis theory. Research data are scenes and dialogues related to research issues. The results of the analysis show that Ryuhei Sasaki's neurotic personality includes; power personality, social recognition or prestige personality, admiring personal personality, perfection and disbelief personality.